Hubungan Pengetahuan, Sikap Dan Perilaku Dalam Memilih Makanan Jajanan Terhadap Kejadian Overweight Pada Siswi SMA Assalam Surakarta - ZULAICHAH, Siti, Fitriana Mustikaningrum, S.Gz, M.Sc, Pramudya Kurnia, STP, M.Agr (2015)
Introduction: Now a days, overweight and obesity being a common problems in the world es pecially women. Overweight and obesity in women due to lifestyle and diet. The results of a preliminary study in Assalam high school showed that the prevalence of young women who were overweight according to 27.4% of the total students. The increasing number of obese today because kids tend to like and choose junk foods. The selection of street food is a form of behavior. Indirectly, the person's behavior is influenced by the attitudes and knowledge. Purpose: The purpose of this study was to determine the relationship between knowledge, attitudes and behavior in snack foods preference on the incidence of overweight in high school Assalam Surakarta. Method: This was an observational study with cross sectional approach. The population in this study was high school students in Assalam, amounting to 253 student. The sample in this study amounted to 64 students. Data analysis using Fisher's exact test and Kolmogorov-Smirnov test. Results: The results showed that the nutritional status of girls mostly in the normal category with 65.6%. The level of student knowledge in snack food preference mostly have a good knowledge level with 92.19%. Students attitude in snack preference food most have a supportive attitude with 84.4%. Student behavior in choosing a snack food most have poor behavior that is 71.9%. Conclusion: Over all, there was was no correlation between knowledge, attitudes and behavior a snack food preference on the incidence of overweight (p= 0.652, p = 0.144 and p = 0.652).